2008
DOI: 10.1242/jcs.022772
|View full text |Cite
|
Sign up to set email alerts
|

Homoeostasis between the GTPase Spg1p and its GAP in the regulation of cytokinesis in S. pombe

Abstract: Cytokinesis in Schizosaccharomyces pombe begins at mitotic entry, when the site of division is defined by formation of the contractile acto-myosin ring (CAR) at the cell cortex. Contraction of the CAR and formation of the division septum are triggered at the end of mitosis by septation initiation network (SIN) proteins associated with the spindle pole body (SPB). SIN signalling requires activation of the GTPase Spg1p, which is regulated by the bipartite GTPase-activating protein (GAP) Byr4p-Cdc16p. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
22
0
2
Order By: Relevance
“…The presence of uninucleate cells with a septum and binucleate cells with more than one septum suggested that Csc1p might participate in inhibiting the SIN. Previous studies have shown that the inactivation of SIN inhibitors leads to septation even in interphase [21, 24, 27]. Consistent with Csc1p participating as an inhibitor of the SIN, 4–6% of S phase arrested csc1 Δ cells contained a division septum (Figure 2B).…”
Section: Resultssupporting
confidence: 78%
“…The presence of uninucleate cells with a septum and binucleate cells with more than one septum suggested that Csc1p might participate in inhibiting the SIN. Previous studies have shown that the inactivation of SIN inhibitors leads to septation even in interphase [21, 24, 27]. Consistent with Csc1p participating as an inhibitor of the SIN, 4–6% of S phase arrested csc1 Δ cells contained a division septum (Figure 2B).…”
Section: Resultssupporting
confidence: 78%
“…However, Cdc7 becomes asymmetrically localized to SPBs in cdc11 phosphomutants, indicating that additional Sid2 targets must exist that contribute to the positive-feedback loop. Candidates for additional Sid2 substrates include Cdc7 itself; the Spg1 GAP component Byr4, which is a heavily phosphorylated protein (Song et al , 1996; Krapp et al , 2008; Johnson and Gould, 2011); the Polo kinase Plo1, which is essential for SIN signaling (Ohkura et al , 1995; Bahler et al , 1998a; Mulvihill et al , 1999); and one or more phosphatase complexes that influence the establishment of SIN asymmetry and SIN signaling (Le Goff et al , 2001; Krapp et al , 2003; Lahoz et al , 2010; Singh et al , 2011). Further study will be required to define the complete repertoire of Sid2 substrates influencing the establishment of asymmetric SIN signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The first-cycle block to septation in spg1-B8, and the fact that Spg1-B8p-GFP is not associated with the SPB (A.K. and V.S., unpublished data; Krapp et al, 2008), argue that SIN signalling is not functional. Nonetheless, we cannot formally exclude that spg1-B8 is a hypomorphic allele and that the presence of the Cdc7p of the SPB in the first mitosis reflects residual Spg1-B8p function.…”
Section: What Regulates the Early-late Transition?mentioning
confidence: 99%